Las necesidades del cuidado de enfermería: criterios para definir requerimientos de personal de enfermería (2000)
ABSTRACT: Supported by theoretical frameworks and different techniques established to define nursing personnel needs, this article tries a novel methodology in which basically quality nursing care required by patients health conditions from a hospital as well as other technical criteria of health care management, guide/shows the definition of the number of required nursing personnel, the level of undergraduate education or any other training required to assure quality nursing care. The author, together with a nursing team, applied the above mentioned methodology in a rural health attention second-level hospital, which has 132 beds and attends patients from different towns with health problems in the five basic specialties and during a certain period during the study. Patients are classified according to nursing attention needs in all hospital services, using experts criteria. This experience is an important starting point for the administration of nursing care.